Exile, Non-Belonging and Statelessness in Grangaud, Jabès, Lubin and Luca No mans language. - Kerr, Greg (Comparative literature and culture, 2021)
Exile, Non-Belonging and Statelessness in Grangaud, Jabès, Lubin and Luca studies the work of four French-language poets to question the relationship between poet, the language they use and the place from which they speak.